'Disease, disaster and despair'? The presentation of health in low- and middle-income countries on Australian television. - Michelle Imison (Public Library of Science (PLoS), 2010)
Background In high-income nations mainstream television news remains an important source of information about both general health issues and low- and middle-income countries (LMICs). However, research on news coverage of health in LMICs is scarce. Principal findings The present paper examines the general features of Australian television coverage of LMIC health issues, testing the hypotheses that this coverage conforms to the general patterns of foreign news reporting in high-income countries and, in particular, that LMIC health coverage will largely reflect Australian interests. We analysed relevant items from May 2005 - December 2009 from the largest health-related television dataset of its kind, classifying each story on the basis of the region(s) it covered, principal content relating to health in LMICs and the presence of an Australian reference point. LMICs that are culturally proximate and politically significant to Australia had higher levels of reportage than more distant and unengaged nations. Items concerning communicable diseases, injury and aspects of child health generally consonant with 'disease, disaster and despair' news frames predominated, with relatively little emphasis given to chronic diseases which are increasingly prevalent in many LMICs. Forty-two percent of LMIC stories had explicit Australian content, such as imported medical expertise or health risk to Australians in LMICs. Significance Media consumers' perceptions of disease burdens in LMICs and of these nations' capacity to identify and manage their own health priorities may be distorted by the major news emphasis on exotic disease, disaster and despair stories. Such perceptions may inhibit the development of appropriate policy emphases in high-income countries. In this context, non-government organisations concerned with international development may find it more difficult to strike a balance between crises and enduring issues in their health programming and fundraising efforts.